UJI PENDAHULUAN DAN KARAKTERISASI SIMPLISIA HERBA PICISAN (Drymoglossum piloselloides (L.) presl) - Lia Fikayuniar; Julia Ratnawati; Yenny Febriani Yun (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2016)
abstrak